E-Market Places Shopeemall on Brand Pixy Official Store Produce Superiority which Competitive - Daulay, Anisya Putri Ertani; Nasution, Muhammad Irwan padli; Sundari, Sri Suci Ayu (LPPM Universitas Bina Bangsa, 2024)
This scientific research aims to determine the scheme of the e-market place conducted by brand pixy store official via shopeemall This study uses a qualitative method by collecting data through the library, and observations originating from book Which concerns title writing as well as through site Internet about brands the.Based on from results writing Which exposed about e market place Which carried out by the official pixy store brand with the goal of making shopping easier with system on line through shopeemall, with exists system service from party store, maintaining the quality of services carried out in the e market place. The e market place system make it easy seller in matter sell product, meanwhile buyer can fulfil his needs according to what he needs, both of these things are done more simple And easy with exists support system technology information, results activity describe that in enter the business world bound in the e-market place necessity training to pixie shop official related from activity Which done in the shopeemall in order to achieve it objective company.